Yucca muscipula (Asparagaceae, Agavoideae), a new species from central Mexico - Ayala-Hernández, María M.; Ríos-Gómez, Ramiro; Solano, Eloy; García-Mendoza, Abisaí (Phytotaxa, 2022)
Yucca muscipula is described and illustrated as a new species endemic to the Barranca de Metztitlán Biosphere Reserve, Hidalgo, Mexico. This species is morphologically related to Y. mixtecana but is shorter, has a stem that lacks branching, and has glaucous leaves that are linear, with papillae on both surfaces and an entire margin, separating into recurved filaments. When dry, the leaves of Y. muscipula persist in the distal portion of the stem after the first flowering. It can grow sympatrically with Y. filifera, that also has a pendulous inflorescence and papillose filaments across entire surface, but from which it differs in several traits including glabrous branches, and larger flowers and fruits.